Trauma-Related Guillain–Barré Syndrome: Systematic Review of an Emerging Concept - Huang, Chuxin; Zhang, Yiliu; Deng, Shuwen; Ren, Yijun; Lu, Wei (Frontiers in Neurology, 2020)
Guillain–Barré syndrome (GBS) is mainly associated with preceding exposure to an infectious agent, although the precise pathogenic mechanisms and causes remain unknown. Increasing evidence indicates an association between trauma-related factors and GBS. Here, we performed a systematic review, summarized the current scientific literature related to the onset of GBS associated with trauma, and explored the possible pathogenesis. A literature search of various electronic databases was performed up to May 2020 to identify studies reporting diverse trauma-related triggers of GBS. Data were extracted, summarized descriptively, and evaluated with respect to possible mechanisms. In total, 100 publications, including 136 cases and 6 case series involving GBS triggered by injury, surgery, intracranial hemorrhage, and heatstroke, met our eligibility criteria. The median age of the patients was 53 [interquartile range (IQR) 45–63] years, and 72.1% of the patients were male. The median number of days between the trigger to onset of GBS symptoms was 9 (IQR 6.5–13). Overall, 121 patients (89.0%) developed post-injury/surgical GBS, whereas 13 (9.6%) and 2 (1.5%) patients had preexisting spontaneous intracranial hemorrhage and heatstroke, respectively. The main locations of injury or surgeries preceding GBS were the spine and brain. Based on available evidence, we highlight possible mechanisms of GBS induced by these triggers. Moreover, we propose the concept of “trauma-related GBS” as a new research direction, which may help uncover more pathogenic mechanisms than previously considered for typical GBS triggered by infection or vaccination.